Pengurusan sisa pepejal di kawasan manjoi, Ipoh bagi tempoh pelaksanaan percubaan penguatkuasaan Akta 672 - Abdullah, Muhammad Nazri (2019)
The legislation of the Solid Waste and Public Cleansing Management Act 2007 (Act 672) by the Ministry of Housing and Local Government (MHLG) is seen as the culmination of the solid waste management evolution in the country. Perak Darul Ridzuan is one of the five states which has yet to fully enforce the application of Act 672, and is still pursuing a probation period exercise in the Manjoi, Ipoh and Pangkor areas even though it has entered its fourth year of implementation. This study was conducted to identify the problems arising during the implementation of the probation period, identifying the views and tendencies of the residents in the Manjoi area on the enforcement of Act 672 and also identifying improvements suggestion that could be implemented in order to improve the solid waste management in the state of Perak in general. The data collection method used was interview with the government leaders and the involved departments, as well as distribution of questionnaires to respondents among the residents in the Manjoi area. Combined qualitative and quantitative analysis methods were conducted to obtain the findings of this study. The results show that there are seven categories of problems encountered during the enforcement of the probation period namely the negative perception among the population, the level of acceptance by the population, the constraints of allocation, the quantity of solid waste, logistics, monitoring and duration of the probation period. The seven categories of these problems have been some of the factors that cause the probation period to be extended to date. It is also noted that residents in the Manjoi, Ipoh are satisfied with the solid waste management services provided by the concession company; Environment Idaman Sdn Bhd and agree that Act 672 should be fully enforced. The study also featured five categories of practical suggestions to be implemented for the purpose of improving the solid waste management system in the state of Perak, that is the policy, education, technology, promotion and facilities. These five categories of proposals require a commitment and seriousness to implement them by all parties involved to ensure that the solid waste management system in Perak is better implemented. Overall, the results of this study can be used as an important source of input to the parties involved to finalize the direction of the implementation of Act 672 in Perak.